NARRATIVE METHOD IN “LES FAUX-MONNAYEURS” OF ANDRÉ GIDE AND “THIẾU QUÊ HƯƠNG” OF NGUYỄN TUÂN FROM THE POINT OF VIEW OF STRUCTURALISM - Trần Thị Bảo Giang (Tạp chí Khoa học Đại học Đà Lạt)
André Gide is one of the famous authors of French literature in particular, of the world literature in the twentieth century in general. “Les Faux-mononayeurs”, his only novel, is classified as one of the best novels of the twentieth century. In this novel, André Gide has introduced a new method of narrative through which the real life is described as its multi-faceted complexity and chaos, etc. Therefore, Gide has put a major step in the development of modern literature era. Receiving and learning French literature along with the Western literature, Nguyen Tuan has shared a number of similarities with André Gide.